Analysis of the Elasticity of Rice Demand for Poor Households in Sirimau District, Ambon City in 2024 - Andre Sapthu; Fredy H. Louhenapessy; Fibryano Saptenno; Desry Louhenapessy; Ummi Duwila; Jani (PT ARRUS Intelektual Indonesia, 2024)
This study aims to analyze the elasticity of rice demand among poor households in Sirimau District, Ambon City. The main focus of this study is the influence of household income, number of family members, the price of Bulog rice, and the price of premium rice on rice consumption among poor households. The analytical method used involves linear regression to identify the relationships between these variables. The results of the study indicate that household income, number of family members, and the price of Bulog rice have a significant positive effect on rice consumption among poor households. Conversely, the price of premium rice does not show a significant effect on rice consumption in this household group. These findings suggest that Bulog rice pricing policies and increasing the income of poor households can be important factors in boosting their rice consumption. This research provides valuable insights for the formulation of more effective food policies to support the welfare of poor households in Sirimau District, Ambon City.